З досвіду підготовки та атестації наукових кадрів вищої технічної школи України - Тверитникова, Олена Євгенівна; Демідова, Юлія Євгенівна (Національний технічний університет "Харківський політехнічний інститут", 2019)
Розглянуто особливості формування системи підготовки й атестації наукового потенціалу вищої технічної школи України впродовж ХХ ст. На основі аналізу нормативно-правових документів встановлено характерні ознаки функціонування інституту аспірантури та докторантури на тлі освітньої державної політики ХХ ст. Акцентовано увагу на ролі професійного середовища вищої технічної школи в підготовці наукових кадрів.

The features of the formation of a system of training and certification of the scientific potential of higher technical schools of Ukraine during the twentieth century. Based on the analysis of regulatory documents, the characteristic features of the functioning of the institute of postgraduate study and doctoral studies are established against the background of educational state policy of the 20th century. Attention is focused on the role of the professional environment of the higher technical school in the training of scientific personnel.
From experience of preparation and certification scientific staff of the higher technical school of Ukraine
Keywords: підготовка аспірантів і докторантів; атестація наукових кадрів; технічні науки; training of graduate students and doctoral students; certification of scientific personnel; technical sciences